Subsequent risk of stillbirth, preterm birth, and small for gestational age: A cross‐outcome analysis of adverse birth outcomes. Issue 6 (18th April 2022) - Bane, Shalmali; Simard, Julia F.; Wall‐Wieler, Elizabeth; Butwick, Alexander J.; Carmichael, Suzan L.
Abstract: Background: Stillbirth, preterm birth, and small for gestational age (SGA) birth have an increased recurrence risk. The occurrence of one of these biologically related outcomes could also increase the risk for another one of these outcomes in a subsequent pregnancy. Objectives: We assessed cross‐outcome risks for subsequent stillbirth, preterm birth, and SGA. Methods: We used live birth and fetal death records to identify singleton, sequential birth pairs in California (1997–2017). Stillbirth was defined as delivery at ≥20 weeks of gestation of a foetus that died in utero; preterm birth as live birth at 20–36 weeks; and small for gestational age as sex‐specific birthweight <10th percentile for gestational age. Risk ratios (RR) were computed using modified Poisson regression and adjusted for potential confounders. Sensitivity analyses included analysing a cohort restricted to primiparous index births and using inverse‐probability censoring weights. Results: Of 3, 108, 532 birth pairs, 16, 668 (0.5%), 260, 596 (8.4%) and 331, 109 (10.7%) of index births were stillborn, preterm and SGA, respectively. Among individuals with an index stillbirth, the adjusted RRs were 1.90 (95% confidence interval [CI] 1.83, 1.98) for subsequent preterm and 1.35 (95% CI 1.28, 1.41) for subsequent SGA. Among those with index preterm birth, the adjusted RRs were 2.02 (95% CI 1.92, 2.13) for stillbirth and 1.42 (95% CI 1.41, 1.44) for SGA. Among those with index SGA, the adjusted RRs were 1.54 (95% CI 1.46, 1.63) for stillbirth and 1.45 (95% CI 1.44, 1.47) for preterm birth. Similar results were reported for sensitivity analyses. Conclusions: Individuals experiencing stillbirth, preterm birth, or SGA in one pregnancy had an increased risk of one of these biologically related outcomes in a subsequent pregnancy. These findings could encourage enhanced surveillance for individuals who experience stillbirth, preterm birth, or SGA and desire a subsequent pregnancy.